2016
DOI: 10.1111/ajco.12602
|View full text |Cite
|
Sign up to set email alerts
|

Validating a proxy for disease progression in metastatic cancer patients using prescribing and dispensing data

Abstract: Our proxy overestimated episodes of disease progression. The proxy's performance is likely to improve if the date of prescribing is used instead of date of dispensing in claims data and by incorporating medical service claims (such as imaging prior to drug changes) in the algorithm. Our proxy is not sufficiently robust for use in real world comparative effectiveness research for cancer medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…From 95 publications initially identified, 52 were excluded either because they did not include a gold standard data source, used administrative claims data as the gold standard, or otherwise did not meet our criteria for inclusion. A total of 43 studies from six countries were identified (Table ). Of these, 72.1% ( n = 31) were published within the last 5 years (ie, since 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 95 publications initially identified, 52 were excluded either because they did not include a gold standard data source, used administrative claims data as the gold standard, or otherwise did not meet our criteria for inclusion. A total of 43 studies from six countries were identified (Table ). Of these, 72.1% ( n = 31) were published within the last 5 years (ie, since 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, five were from Australia and one each from Japan and South Korea. Among Australian studies, cancer outcomes included pancreatic and periamupullary cancers, prostate cancer, colorectal and lung cancer, metastatic cancer patients, and gastro‐intestinal cancer . A variety of gold standard sources were used: registry data (1), medical records (2), and other data sources (cancer surveys; 2).…”
Section: Type Of Outcomes Validatedmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the studies included in this review used the initiation of a medicine as a proxy for the development of an adverse event, other studies have utilised longer-term patterns in dispensing data to indicate safety issues. For example Joshi et al [ 79 ] utilised changes in drug treatment to infer disease progression or treatment failure in cancer. Another study used patterns of accumulation of cardiovascular diseases, indicated by medications used to treat them, to investigate the effectiveness of modifiable disease progression in statin initiators [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herceptin Program and PBS data do not contain specific information identifying disease progression and proxies for progression using these datasets have been shown to be unreliable. [ 15 ] It is recommended practice to change a chemotherapeutic agent at the time of disease progression, [ 16 ] and during the study period it was also common practice to continue trastuzumab treatment beyond disease progression but change chemotherapeutic agents. [ 17 ] The use of chemotherapy agents with trastuzumab following treatment with a taxane in our cohort likely represents trastuzumab continued beyond progression, however, we did not attempt to identify specific instances of the non-adherent practice of continuing trastuzumab use beyond disease progression.…”
Section: Methodsmentioning
confidence: 99%